Optimization of a tandem ion exchange—extraction chromatographic scheme for the recovery of strontium from raw urine. Issue 1 (2nd January 2020) - Kaminski, Michael; Sandi, Giselle; Dietz, Mark; Park, Anthony
ABSTRACT: A previously reported ion-exchange/extraction chromatographic scheme for the recovery of radiostrontium from urine for subsequent determination is systematically optimized to minimize reagent consumption, enhance system reusability, and maximize sample throughput. In addition, a preliminary assessment of the effect of mobile phase flow rate on strontium uptake is described. The results show that the tandem system can be re-used without loss of performance, and that the rate at which samples can be processed by the system is ultimately limited by the time required for regeneration of the ion-exchange column and the kinetics of metal ion uptake on the extraction chromatographic sorbent. Abbreviations: LOV: lab on valve CDC: Center for Disease Control and Prevention EXC: extraction chromatography EDTA: ethylenediaminetetraacetic acid MDL: method detection limit MSA: methanesulfonic acid